2018
DOI: 10.2196/jmir.9605
|View full text |Cite|
|
Sign up to set email alerts
|

Alcohol Consumption Reduction Among a Web-Based Supportive Community Using the Hello Sunday Morning Blog Platform: Observational Study

Abstract: BackgroundAlcohol misuse is a major social and public health issue in Australia, with an estimated cost to the community of Aus $30 billion per annum. Until recently, a major barrier in addressing this significant public health issue is the fact that the majority of individuals with alcohol use disorders and alcohol misuse are not receiving treatment.ObjectiveThis study aimed to assess whether alcohol consumption changes are associated with participation in Hello Sunday Morning’s blog platform, an online forum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 51 publications
0
22
1
Order By: Relevance
“…Thus, many of our participants (69%) were classified as probably dependent on the AUDIT whereas the respective figure reported by Riper et al was 22%, but they also reported that 34% were heavy drinkers (defined as >35/50 standard drinks for females or males) [13]. Also notable was the high prevalence of women in our trial, representing 71% of participants compared with typical values of about 50% [12,13] and even compared to the previous assessment of Hello Sunday Morning clients (64%) [19]. There are concerns that eHealth alcohol interventions may not be as effective with women as men [13].…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Thus, many of our participants (69%) were classified as probably dependent on the AUDIT whereas the respective figure reported by Riper et al was 22%, but they also reported that 34% were heavy drinkers (defined as >35/50 standard drinks for females or males) [13]. Also notable was the high prevalence of women in our trial, representing 71% of participants compared with typical values of about 50% [12,13] and even compared to the previous assessment of Hello Sunday Morning clients (64%) [19]. There are concerns that eHealth alcohol interventions may not be as effective with women as men [13].…”
Section: Discussioncontrasting
confidence: 40%
“…The Daybreak program lies within the more extensive group. Previously, the extent of engagement with the Hello Sunday Morning program (eg, in terms of blog posts, blog shares, following other participants) has been shown to correlate with improved outcomes (ie, reduced AUDIT scores) [19]. Despite the low overall level of engagement (see Table 2), these measures still predicted a range of improved outcomes (eg, in AUDIT–C score, in EUROHIS-QOL score with blog comments about alcohol use, and in blog shares at one month).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In study 2, we sought to determine whether it was possible to conduct a trial evaluating the impact of Internet intervention websites that we did not have direct control over. After examining several free-of-charge online interventions for suitability for an American audience (i.e., MTurk workers) we chose Hello Sunday Morning (HSM) [25], comparing it to Check Your Drinking (CYD; public access version) as the active control and to a no intervention control condition. The objectives of study 2 were to test whether it was possible to conduct the trial in such a way that the participants demonstrated that they had accessed the intervention, and to examine whether there was any evidence of impact of the intervention.…”
Section: Study 2 Introductionmentioning
confidence: 99%
“…6 Additionally, engagement with web-based interventions can impact patient decisions such as alcohol abstinence and are being tested for encouraging a heart healthy lifestyle. 9,10 The men with USD in our study often expressed that hearing from other men with similar experiences was helpful and were grateful for the responses. Quality of information in online health forums is generally good, with physicians and laypeople rating only rare instances of extremely poor information.…”
Section: Discussionmentioning
confidence: 82%